2010
DOI: 10.4049/jimmunol.0902724
|View full text |Cite
|
Sign up to set email alerts
|

Cell Surface Heparan Sulfate Proteoglycans Influence MHC Class II-Restricted Antigen Presentation

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 41 publications
(40 reference statements)
0
15
0
Order By: Relevance
“…As we previously observed that a hybrid protein containing an HS-binding domain is more effectively captured by APCs and thus stimulates Th cells more efficiently (14), we decided to assess whether a similar behavior is observed for a wild-type protein intrinsically endowed with HS-binding ability. The observation that DT and CRM197 contain four clusters of basic residues prompted us to postulate that these proteins may both be able to bind HS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we previously observed that a hybrid protein containing an HS-binding domain is more effectively captured by APCs and thus stimulates Th cells more efficiently (14), we decided to assess whether a similar behavior is observed for a wild-type protein intrinsically endowed with HS-binding ability. The observation that DT and CRM197 contain four clusters of basic residues prompted us to postulate that these proteins may both be able to bind HS.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we recently showed that an Ag previously coupled to an HSPG ligand can interact with HSPGs expressed on the surface of APCs. These molecules can then act either as receptors or as coreceptors and thus allow an increase in MHC class II-restricted presentation (14).…”
mentioning
confidence: 99%
“…Strong candidates are HSPGs, which are involved in the endocytosis of 3D8 scFv by HeLa cells (13) and in the endocytosis of CPPs, which contain multiple cationic amino acid residues similar to 3D8 scFv (36). It is reported that clustering of HSPGs triggers cytoskeletal remodeling and internalization pathways, and that HSPGs promote MHC class II-restricted Ag presentation by acting as coreceptors during Fcg-RII-mediated Ag presentation (37,38). However, in the current study, endocytosis of 3D8 scFv was not affected by treatment with heparinase III (which cleaves heparan sulfate of HSPGs; data not shown), despite the inhibition of 3D8 scFv endocytosis in the presence of heparin, a competitor of HSPGs.…”
Section: Discussionmentioning
confidence: 99%
“…Besides being rapidly internalised via endocytosis (Tyagi et al, 2001), heparan sulphate is probably also involved in the initial binding step before internalisation (Ferrari et al, 2003). It can also act as a coreceptor for endocytosis (Leonetti et al, 2010). Interestingly, other glycosaminoglycans such as chondroitin sulphate and dermatan sulphate have been ruled out in the binding/internalisation of full length tat 1-86 (Tyagi et al, 2001) and tat 37-57 (Leonetti et al, 2010), but not for the shorter tat 48-60 (Sandgren et al, 2002).…”
Section: Tatmentioning
confidence: 99%
“…It can also act as a coreceptor for endocytosis (Leonetti et al, 2010). Interestingly, other glycosaminoglycans such as chondroitin sulphate and dermatan sulphate have been ruled out in the binding/internalisation of full length tat 1-86 (Tyagi et al, 2001) and tat 37-57 (Leonetti et al, 2010), but not for the shorter tat 48-60 (Sandgren et al, 2002). Classical endocytosis is an energy-and ATP-dependent mechanism.…”
Section: Tatmentioning
confidence: 99%